ANALISIS PERSEPSI MAHASISWA TERHADAP ADANYA AKUNTANSI FORENSIK - Manurung, Tya Yuli R. (Universitas Ahmad Dahlan, 2018)
This study aims to analyze students' perceptions about forensic accounting. As a tool to accelerate the eradication of corruption and combating fraud, forensic accounting is included in the accounting education curriculum, but forensic accounting has not received serious attention from the university. This study analyzes whether there are differences in perceptions about forensic accounting between accounting students of Faculty of Economics and Business, Universitas Sumatera Utara (FEB USU) and Faculty of Sharia, Universitas Islam Negeri Sumatera Utara (FS UINSU). This research is an empirical study with purposive sampling technique in data collection. The sample in this study were 102 respondents, consisting of 67 accounting students of FEB USU and 35 accounting students of FS UINSU. The results showed that there was a significant difference between the perception of accounting students of FEB USU and FS UINSU on forensic accounting.